New Caridina (Atyidae - Crustacea) shrimps collected from Hai Van mountain pass (Thua Thien - Hue province) - Tu, Do Van; Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
﻿For the first time, Caridina (Atyidae - Crustacea) shrimps has been collected from streams highgly located in Hai Van Mountain Pass, between Thua Thien - Hue and Da Nang provinces, central Vietnam. Among them, two species are described as new for science: Caridina haivanensis sp. nov. and Caridina pseudoflavilineata sp. nov. 1. Caridina haivanensis sp. nov. Rostrum short, approximately reaching the end of the 1st antennular peduncule segment,. The dorsal border bearing frequently 0-3 teeth, the ventral havng no teeth or only 1. No teeth on the carapace. Endopod I of the male kidney- shaped, distal appendix overeaching its extremity. Endopod II with stout finger ﻿shaped, appendix masculina extending beyond the middle of Endopod II. Appendix interna not reaching the middle of appendix masculina. Telso acutely ending. Big eggs, dimensions : 1.1 - 1.3 · 0.75 - 0.8 m/m. 2. Caridina pseudoflavilineata sp. nov. Shrimp of small size. Rostrum lanceolate in form reaching the end of the 2nd or 3rd antennular peduncule segment. The dorsal border bearing 9-12 teeth, with 3-4 teeth on the carapace. The ventral border with 3-4 teeth. Endopod I of the male coniform, distal appendix overeaching its extremity. Endopod II with finger form,appendix masculina extending beyond the middle of Endopod II. Appendix interna short. Eggs dimensions: 1.1 · 0.75 m/m.